Religion in education: is there yet another solution? - Walt, J. L. van der (Koers, 2010)
As colleague and co-worker of Professor Bennie van der Walt, the author has been in a position for several decades now to apply some of Bennie van der Walt’s philosophical and theological insights in the field of education. Professor Van der Walt’s recent discussion and critique of secularism and of religious tolerance enables the author to analyse the educational situation in South Africa and elsewhere with particular emphasis on policies about religion in/and education. These investigations lead him to conclude that most education systems seem to resort to secular public-private and worldly-sacral dualistic policies for addressing the problem of potential religious conflict in schools. After considering the Dutch policy of (increasing) pillarisation and the South African policy of banning confessional aspects of religious education to the private spheres of citizens’ lives, he proposes a solution based on the concept of institutional religious and life-conceptual identity. This approach can also lead to religious tolerance among learners in schools (as mooted by Bennie van der Walt and others) while circumventing the pitfalls of secularism.